1994
DOI: 10.1002/macp.1994.021950222
|View full text |Cite
|
Sign up to set email alerts
|

Particle growth in butadiene emulsion polymerization, 4. The promoting effect of mercaptans

Abstract: SUMMARYThe observation that b,utadiene emulsion polymerizations in the presence of fatty acid emulsifiers need minimal amounts of tertiary or n-dodecanethiols to polymerize at a reasonable rate is often referred to as the promoting effect of mercaptans and is evaluated in this paper.Experimental evidence is presented which shows that fatty acid emulsifiers can actively reduce the average number of radicals per particle. In this paper it will be shown that three components are necessary for retardation of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the thermally-initiated emulsion polymerization of isoprene and butadiene, mercaptans such as tert-dodecyl mercaptan (t-DM) have been found to be essential additives to achieve high conversion [8,26,48]. It has been suggested that the mercaptan enhances entry efficiency: through chain transfer from a sulfate or oligomeric isoprene radical to the thiol, which may enter micelles/particles directly, and/or form an entering species after fewer propagation steps than would otherwise be the case [23]. The z value of the resulting t-dodecyl terminated radical is expected [49] to be very competitive with propagation due to the lower water-solubility of t-DM, 3 £ 10 25 M, compared to that of isoprene, 8.2 £ 10 23 M [50].…”
Section: Mechanistic Preceptsmentioning
confidence: 98%
“…In the thermally-initiated emulsion polymerization of isoprene and butadiene, mercaptans such as tert-dodecyl mercaptan (t-DM) have been found to be essential additives to achieve high conversion [8,26,48]. It has been suggested that the mercaptan enhances entry efficiency: through chain transfer from a sulfate or oligomeric isoprene radical to the thiol, which may enter micelles/particles directly, and/or form an entering species after fewer propagation steps than would otherwise be the case [23]. The z value of the resulting t-dodecyl terminated radical is expected [49] to be very competitive with propagation due to the lower water-solubility of t-DM, 3 £ 10 25 M, compared to that of isoprene, 8.2 £ 10 23 M [50].…”
Section: Mechanistic Preceptsmentioning
confidence: 98%
“…Rubbers based on butadiene were also studied quite intensively from the late 1950s to the early 1990s in solution and in emulsions [35,[66][67][68][69][70][71][72].…”
Section: Free Radical Polymerizationmentioning
confidence: 99%
“…For increasing the final conversion in emulsion polymerization of isoprene, Cheong et al added t-DM to the reaction mixture [9]. It is believed that mercaptan enhances entry efficiency in particles through chain transfer from a sulfate (when a persulfate is used as initiator) or oligomeric isoprene radical to the thiol, which may enter micelles/particles directly and/or form an entering species after fewer propagation steps in comparison with those required for oligomeric isoprene radicals [15]. In our case, in spite of using t-DM, final conversion after 24 h reaction was about 35%.…”
Section: Resultsmentioning
confidence: 99%